METODE PEMBIASAAN DALAM PEMBINAAN SHALAT BERJAMAAH DAN IMPLIKASINYA TERHADAP PENANAMAN BUDAYA BERAGAMA SISWA SMP NEGERI 2 KABAWETAN - Aisyahnur Nasution (IAIN Bengkulu, 2019)
This research is based on the application of habituation methods in fostering prayer in congregation to Kabawetan 2 Public Middle School students. This junior high school is a school whose education is important for instilling disciplinary character, to prevent negative behavior of students who will be directed, trained to fortify students from negative influences so that researchers choose habituation methods in congregational prayer formation and their implications for planting culture of Kabawetan 2 Public Middle School students. This research method is qualitative research. The research subjects were principals, deputy principals, pie masters, PNK teachers, picket teachers and students of Kabawetan Public Middle School 2, collecting data using the main techniques of observation, interviews, documentation, then data processing techniques using data reduction data validity, data display, data analysis, and for interpestation of data by interpreting it in the form of a description. The results of the research on the application of habituation methods in prayer prayer at the Kabawetan State Junior High School 2 is a policy of habituation methods agreed by stakeholders of Kabawetan Public High School 2. by all students together in the Dhuha prayer and alternating on the midnight prayer according to a predetermined schedule, the application of this method is good, to instill religious values in children, because habituation will continue to stick in the minds of children until they carry out habituation pious charity and noble character and the implications of prayer in congregation for the religious culture of students at Kabawetan 2 Public Middle School is a routine activity that must be followed by students who are already scheduled, students who do not take part in prayer activities are punished by reading the verses of the Qur’an halat congregation is used as a school culture, because the school wants to instill character in students with the values of prayer in congregation, namely the value of ‘ubudiyah, moral values of al-karimah (positive mindset, mission statement, thinking and acting strategically, togetherness, tawadlu’, optimistic and independent, networking, disciplinary values (nizhamiyah).